INCREASING THE FUNCTIONAL EFFECTIVENESS OF MUNICIPAL SERVICE SYSTEMS THROUGH MUNICIPAL-PRIVATE PARTNERSHIP MECHANISMS - E. V. Atueva; M. N. Isalova; M. M. Shabanova (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. Due to the issue of public utility development becoming a key concern for many Russian municipalities, this study aims to evaluate methods for increasing the efficiency of municipal services. The reason for this is the severe dilapidation of the physical infrastructure. Given the limited budget, the question inevitably arises as to how to most effectively spend the funds available and at the same time solve emerging urban infrastructure problems. Method. Use of the municipal-private partnership mechanism can significantly reduce the burden on the municipal budget.The method of paired comparisons of alternative models is recommended on the basis of the choice of the municipal-private partnership model.Alternative models of municipal-private partnership are ranked in preference against a plurality of predetermined comparison criteria. Results.The results of an analysis of the development of municipal services in the city of Makhachkala are presented. The necessity for municipal-private partnerships to be developed in the area of urban public utilities is substantiated. A structural-logical model of municipal-private partnership in the communal area of the city is proposed with the concrete functions assigned to each of the members of the municipal-private partnership. Conclusion. It is demonstrated that municipal-private partnerships serve as a means of optimising the performance of municipal functions with respect to the seamless provision of quality housing and communal services to the city's population and creation of a favourable urban environment. Use of the proposed method allows alternative models to be evaluated and the optimal model of municipal-private partnership selected for the implementation of a specific project in the area of urban public utilities.